A history of the coal miners of the United States. From the development of the mines to the close of the anthracite strike of 1902. Including a brief sketch of early British miners (Greenwood Press, 1970)
Photomechanical reprint of the ed.: Columbus, Ohio, Tranger Printing Co., 1905?